Nine years of tracking data reveal high post‐breeding survival of radiomarked male woodcock in Rhode Island - Colby R. Slezak; Dylan L. Bakner; Roger J. Masse; Scott R. McWilliams (Wildlife Society Bulletin)
Abstract To stabilize or increase populations of declining wildlife, it is essential to identify drivers of variation in survival. We evaluated male American woodcock (Scolopax minor) post‐breeding survival and assessed the extent to which age, ordinal date, precipitation, and landscape habitat quality (indexed by relative probability of use scores) influenced post‐breeding survival. Overall post‐breeding survival estimates for 196 radiomarked male woodcock from May to September were high (i.e., 0.894, 95% credible intervals = 0.760–0.982), and the 4 covariates we assessed did not influence daily survival rate. The high post‐breeding survival of woodcock during our study was consistent with the other estimates for the post‐breeding period and is similar to other adult survival estimates throughout much of the annual cycle.